Revision of the Neotropical species of the subgenus Atrichopogon (Psilokempia) (Diptera: Ceratopogonidae) - Spinelli, Gustavo R.; Marino, Pablo I.; Huerta, Herón (Zootaxa, 2015)
This revision of the midges in the subgenus Psilokempia Enderlein of Atrichopogon Kieffer provides a brief description of the subgenus, diagnoses, descriptions, illustrations and a key to adult males and females of the 17 species from the Neotropical region, as well as distributional records of both new and previously described species. Six new species are described and illustrated: A. arti, A. javieri, A. longirostris, A. nahuelbutensis, A. sergioi and A. woodruffi (n. spp.). The type materials of all previously known Neotropical species except A. penicillatus Delècolle & Rieb were examined. Atrichopogon altivolans Macfie, A. aridus Spinelli & Marino, A. domizii Spinelli, A. glaber Macfie, A. gordoni Macfie, A. insigniventris Macfie, A. pectinatus Macfie and A. penicillatus are redescribed and illustrated, and notes on the types of A. echinodes Macfie, A. harrisi Macfie and A. sanctaeclarae Macfie are provided. Lectotypes are designated for A. glaber, A. insigniventris and A. pectinatus. The previously unknown males of A. altivolans, A. pectinatus and A. penicillatus are described and illustrated, and A. fimbriatus Macfie is recognized as a junior synonym of A. gordoni.